FOUNTAINS IN MAGMA CHAMBERS - Campbell Ia.H.; Turner J.S. (My University, 1989)
Cyclic layering is a common feature of the ultramafic zone of layered intrusions and is usually attributed to the entry of new pulses of dense magma into the chamber. Since the crystallization of olivine and bronzite lowers the density of the magma, a new pulse of the parent magma will be denser than the fractionated magma in the chamber. If the new pulse enters with excess momentum it will initially rise up into the host magma to form a fountain, then fall back around the feeder when negative buoyancy forces overcome the initial momentum of the pulse. Laboratory experiments using aqueous solutions with both point and line sources have been conducted to obtain a quantitative understanding of the fluid-dynamical processes that are important in fountains. It is observed that convection within the fountain is highly turbulent, resulting in appreciable entrainment of the host magma. A gravity-stratified hybrid layer develops at the floor and this breaks up into a series of double-diffusive convecting layers if the new pulse is hotter than the host magma. The number of layers that form depends on a number of factors, especially